2005
DOI: 10.4049/jimmunol.174.1.310
|View full text |Cite
|
Sign up to set email alerts
|

IL-2 Overcomes the Unresponsiveness but Fails to Reverse the Regulatory Function of Antigen-Induced T Regulatory Cells

Abstract: Intranasal administration of peptide Ac1–9[4Y], based on the N-terminal epitope of myelin basic protein, can induce CD4+ T cell tolerance, and suppress experimental autoimmune encephalomyelitis induction. The peptide-induced regulatory T (PI-TReg) cells failed to produce IL-2, but expressed IL-10 in response to Ag and could suppress naive T cell responses in vitro. Analysis of Jak-STAT signaling pathways revealed that the activation of Jak1, STAT3, and STAT5 were induced in tolerant T cells after Ag stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 48 publications
2
37
0
Order By: Relevance
“…After repeated Ag stimulation, effector T cells become tolerant (12). We found that tolerance is not due to loss of Ag-specific T cells, but rather downregulation of proximal TCR signaling pathways following Ag stimulation (13,14), which resembles the findings from chronic viral infections (4). We found that an increase in the amount of Ag presented by activated dendritic cells (DC) cannot reverse tolerance (13).…”
Section: H Epatitis B Virus (Hbv) Is a Noncytopathic Hepadnavirussupporting
confidence: 47%
See 2 more Smart Citations
“…After repeated Ag stimulation, effector T cells become tolerant (12). We found that tolerance is not due to loss of Ag-specific T cells, but rather downregulation of proximal TCR signaling pathways following Ag stimulation (13,14), which resembles the findings from chronic viral infections (4). We found that an increase in the amount of Ag presented by activated dendritic cells (DC) cannot reverse tolerance (13).…”
Section: H Epatitis B Virus (Hbv) Is a Noncytopathic Hepadnavirussupporting
confidence: 47%
“…We found that tolerance is not due to loss of Ag-specific T cells, but rather downregulation of proximal TCR signaling pathways following Ag stimulation (13,14), which resembles the findings from chronic viral infections (4). We found that an increase in the amount of Ag presented by activated dendritic cells (DC) cannot reverse tolerance (13). However, addition of IL-2 can effectively overcome tolerance and restore the full activation of T cells in response to Ag stimulation (13).…”
Section: H Epatitis B Virus (Hbv) Is a Noncytopathic Hepadnavirusmentioning
confidence: 51%
See 1 more Smart Citation
“…The relatively high degree of STAT3 phosphorylation is in line with recent data indicating that increased levels of STAT3 protein are a feature of allotolerant cells, 28 and that signaling via the immunosuppressive cytokine IL-10 requires STAT3 activation. 29,30 The phenotype of the Treg cells induced by FK778 was further characterized by the presence of CD45RO and lack of CD27 and CD62L expression. This fits an effector-memory phenotype, making these cells suitable to act at a site of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Under experimental conditions in murine models, tumor-DC vaccinations can overcome tolerance and enhance therapeutic outcome (24). IL-2 and IFN-a can also contribute in overcoming these regulatory pathways (25,26). Other inhibitory loops include both natural killer T cells and a subpopulation of inhibitory DCs (27,28).…”
mentioning
confidence: 99%